1988
DOI: 10.1016/0012-1606(88)90237-0
|View full text |Cite
|
Sign up to set email alerts
|

Spectrin and calmodulin in spreading mouse blastomeres

Abstract: The role of spectrin and its association with calmodulin in spreading mouse blastomeres was investigated. Embryonic spectrin binds 125I-calmodulin in a calcium-dependent fashion in the blot overlay technique. Double-labeling experiments show coordinate redistribution of spectrin and calmodulin in blastomeres preparing to undergo active spreading movement. At this stage cortical spectrin staining is lost from the region of cell-substrate contact and spectrin and calmodulin become concentrated in two structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…It is also the site of formation of tight junctions (see below). Within the contact zone itself, microvilli are absent, while in the underlying cytocortex, microfi1aments, myosin, and spectrin appear to be reorganized Reima & Lehtonen 1985;Lehtonen & Reima 1986;Sobel et al 1988). Intercellular contacts become more extensive at the 8-cell stage as the blastomeres acquire the ability to deform and fl atten on each other, and it is likely that many of the changes associated with the contact zone are exaggerated versions of those seen at focal contact points during earlier cleavage (see above).…”
Section: Actin and Actin-associated Proteinsmentioning
confidence: 91%
“…It is also the site of formation of tight junctions (see below). Within the contact zone itself, microvilli are absent, while in the underlying cytocortex, microfi1aments, myosin, and spectrin appear to be reorganized Reima & Lehtonen 1985;Lehtonen & Reima 1986;Sobel et al 1988). Intercellular contacts become more extensive at the 8-cell stage as the blastomeres acquire the ability to deform and fl atten on each other, and it is likely that many of the changes associated with the contact zone are exaggerated versions of those seen at focal contact points during earlier cleavage (see above).…”
Section: Actin and Actin-associated Proteinsmentioning
confidence: 91%
“…Other actin filament-binding proteins thought to bind and be regulated by holocalmodulin include ␤ spectrin (27), calponin (28), and utrophin (29), although some controversy exists regarding the role of holocalmodulin binding for dystrophin (29,30) or ␣-actinin functions (31,32). Many known calmodulin-binding proteins have basic amphipathic helix structures with positively charged amino acids interspersed among conserved hydrophobic stretches (11,33).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CaM can bind to many other CHdomain proteins, even though these generally do not posses IQ-motifs. These proteins include calponin (10,11), spectrin (12), dystrophin (13), and filamin A (14), in which CaM modulates the Ca 2ϩ dependence of actin binding (13)(14)(15). Some CHdomain proteins, such as IQGAP, also contain IQ-motifs, though these are located outside of the CH-domain region of the protein (16).…”
mentioning
confidence: 99%